Radiative feedbacks in tropical organized convection and the Madden-Julian oscillation - Hsiao, Wei-Ting, author; Maloney, Eric D., advisor; Rugenstein, Maria A. A., committee member; Kummerow, Christian D., committee member; Randall, David A., committee member; Mueller, Nathaniel D., committee member (Colorado State University. Libraries, 2024)
The organization of tropical deep convection is supported by radiative feedbacks, in which high clouds and moisture anomalies associated with convection imposes anomalous longwave (LW) radiative heating in the atmosphere, further supporting convection. Despite an abundance of studies using numerical simulations, the interactions between tropical convective organization, radiative feedbacks, and the large-scale atmospheric environment have not been comprehensively examined in real-world observations. The present dissertation examines such interactions among tropical mesoscale organized convection, radiative feedbacks, and the Madden-Julian oscillation (MJO) using a set of observation-derived data products, including retrievals using spaceborne satellites and ground-based precipitation radar, along with combined products and reanalyses. The main findings in each chapter are summarized as follows: (1) higher sea surface temperature and stronger low-level wind shear strength enhance tropical mesoscale convective activity, increasing cirrus cloud cover and LW heating generated per unit precipitation. (2) the estimation of LW cloud-radiative feedback (LW CRF), defined as the LW cloud-radiative heating produced per unit precipitation, is sensitive to the precipitation data set used. (3) radiatively driven circulation and the associated moistening effects in the MJO can be derived in a weak-temperature-gradient framework and a linear baroclinic model. The result suggests that LW heating moistens the MJO more efficiently than the total apparent heat source, while shortwave (SW) radiative effects dry the MJO. (4) The LW CRF of the MJO is spatially inhomogeneous, with stronger feedbacks over the tropical Indian ocean and to the northwest of Australia, but weaker feedbacks over the tropical western and central Pacific. The spatial pattern may be determined by the spatial distribution of preferred convective types and precipitation efficiency.
Keywords: convective organization; tropical convection; the Madden-Julian oscillation; cloud radiative effects